'Enabled to play, enabled to explore': children's civic engagement, literacies, and teacher professional learning. Issue 5 (2nd September 2020) - McKee, Lori; Heydon, Rachel
ABSTRACT: Drawing from a multiple-case study of professional learning in literacy, this article presents vignettes from a Grade 1 classroom where the professional learning focused on multimodal literacy pedagogies that combined digital and print-based resources to expand children's meaning-making. Linking children's opportunities for expansive literacy options and civic engagement, we focus on a lesson cycle in one teacher's engagement in the learning. We highlight how the teacher's pedagogy of exploration positioned children as capable meaning makers and how the children's innovative literacy practices informed the teachers' understandings of literacy pedagogies. These findings forward grounded examples of classroom spaces for children's meaning-making and civic engagement that are co-produced by multimodal and flexible pedagogies where children act as curricular-informants.